Epithelial barrier assembly requires coordinated activity of multiple domains of the tight junction protein ZO-1 - Rodgers, Laurel S. (The Company of Biologists, 2013)
Tight junctions (TJs) regulate the paracellular movement of ions, macromolecules and immune cells across epithelia. Zonula occludens (ZO)-1 is a multi-domain polypeptide required for the assembly of TJs. MDCK II cells lacking ZO-1, and its homolog ZO-2, have three distinct phenotypes: reduced localization of occludin and some claudins to the TJs, increased epithelial permeability, and expansion of the apical actomyosin contractile array found at the apical junction complex (AJC). However, it is unclear exactly which ZO-1 binding domains are required to coordinate these activities. We addressed this question by examining the ability of ZO-1 domain-deletion transgenes to reverse the effects of ZO depletion. We found that the SH3 domain and the U5 motif are required to recruit ZO-1 to the AJC and that localization is a prerequisite for normal TJ and cytoskeletal organization. The PDZ2 domain is not required for localization of ZO-1 to the AJC, but is necessary to establish the characteristic continuous circumferential band of ZO-1, occludin and claudin-2. PDZ2 is also required to establish normal permeability, but is not required for normal cytoskeletal organization. Finally, our results demonstrate that PDZ1 is crucial for the normal organization of both the TJ and the AJC cytoskeleton. Our results establish that ZO-1 acts as a true scaffolding protein and that the coordinated activity of multiple domains is required for normal TJ structure and function.